Bioaccumulation of heavy metals in tissues of selected fish species from Ganga river, India, and risk assessment for human health. Issue 4 (19th May 2019) - Maurya, Pradip Kumar; Malik, D. S.
ABSTRACT: The study measured the concentration of Cd, Cr, Pb, Cu, and Zn in various fish tissues (muscle, gills, and liver) of 18 fish species ( C. gachua, C. marulius, C. punctatus, C. nama, C. ranga, H. fossilis, C. batrachus, P. ticto, P. phutunio, L. rohita, L. calbasu, L. gonius, T. putitora, T. tor, R. rita, G. chapra, H. ilisa, and N. botia ) collected from Ganga river. It is the survey regarding metal concentration in fish tissues increasing day by day. The metal concentration in different fish tissues varied on the following range: Cu (0.45–8.54 µg/g wet wt), Zn (0.07–2.2 µg/g wet wt), Pb (0.20–2.62 µg/g wet wt), Cd (0.07–2.32 µg/g wet wt), and Cr (0.09–1.74 µg/g wet wt). The results show the concentration of Pb, Cd, and Cr metals to be higher than internationally recommended standard limits (as determined by the WHO and FAO) and other similar studies. Generally, higher concentrations of metals were found in liver and gills than muscles. Despite lower estimated daily intake (EDI) of fish in the area (per recommended daily allowance guidelines), values of daily average consumption were lower than the recommended values by FAO/WHO/EFSA, and in fish samples these were below the provisional permissible levels for human consumption. The continuous exposure to heavy metals has been linked to the development of mental retardation, kidney damage, various cancers, and even death in instances of very high exposure in human body.